2018
DOI: 10.1016/j.cogpsych.2018.03.002
|View full text |Cite
|
Sign up to set email alerts
|

The role of domain-general cognitive resources in children’s construction of a vitalist theory of biology

Abstract: Some episodes of learning are easier than others. Preschoolers can learn certain facts, such as "my grandmother gave me this purse," only after one or two exposures (easy to learn; fast mapping), but they require several years to learn that plants are alive or that the sun is not alive (hard to learn). One difference between the two kinds of knowledge acquisition is that hard cases often require conceptual construction, such as the construction of the biological concept alive, whereas easy cases merely involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 50 publications
5
23
0
Order By: Relevance
“…Vosniadou et al also measured children's executive function skills -set-shifting ability and inhibitory control -and found that children with higher executive function were more likely to categorize the target items by their scientific properties and were faster to do so (see also Bascandziev et al, 2018;Tardiff et al, 2020). These findings echo our finding that children with higher cognitive reflection were more accurate at verifying counterintuitive scientific ideas, and they raise questions about the relation between cognitive reflection and executive function.…”
Section: Discussionsupporting
confidence: 82%
“…Vosniadou et al also measured children's executive function skills -set-shifting ability and inhibitory control -and found that children with higher executive function were more likely to categorize the target items by their scientific properties and were faster to do so (see also Bascandziev et al, 2018;Tardiff et al, 2020). These findings echo our finding that children with higher cognitive reflection were more accurate at verifying counterintuitive scientific ideas, and they raise questions about the relation between cognitive reflection and executive function.…”
Section: Discussionsupporting
confidence: 82%
“…Importantly, children's inhibitory control skills were specifically related to their performance on comparisons that had misleading information, for example, trials where the largest fraction had the smallest denominator. These results add to the growing evidence suggesting that inhibitory control plays a role in reducing the impact of misleading information in numerosity processing more generally (Gilmore et al, 2013;Norris & Castronovo, 2016) and even in scientific reasoning when content contradicts learners prior knowledge (Bascandziev, Tardiff, Zaitchik, & Carey, 2018;Brookman-Byrne, Mareschal, Tolmie, & Dumontheil, 2018). Here, we aim to investigate, for the first time in children, whether inhibitory control is related to non-symbolic proportional reasoning, especially in contexts with misleading discrete information.…”
Section: Contributions Of Inhibitory Control To Proportional Reasoningmentioning
confidence: 90%
“…Working memory and inhibition together facilitate efficient shifting between tasks or mental states (Best and Miller 2010). These three abilities, collectively termed executive functions (Miyake et al 2000), underlie the ability to reason as well as to test and revise mental models, which are crucial for the acquisition of complex concepts (Bascandziev et al 2018;). Children's deficits in executive functions can therefore be expected to impinge upon the effectiveness of all GLSs, as the construction of relations between to-be-learned information and prior knowledge, as well as the integration of the new information, requires at least basic reasoning abilities (Zaitchik et al 2014).…”
Section: A Brief Developmental-science Perspective On Learning Stratementioning
confidence: 99%